Electrical and structural properties of flash evaporation InSb thin films - Al-Ani, S.K.J.; Obaid, Y.N.; Kasim, S.J.; Mahdi, M.A. (Universiti Malaysia Perlis, 2009)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008 & vol. 2; issue 1, 2009.